Efectos de la aplicación de tres dosis de compost en dos variedades de frejol (Phaseolos vulgaris L.) en el cantón Bolívar provincia del Carchi 2017 - Itás Reyes, Manuel Mesías (2017)
VII. SUMMARY At Bolívar canton, Carchi province, farmers are facing series of problems like: the considerable decrease in the organic matter existing in the soil which is causing an exaggerated increase in production costs so it is necessary to make amendments to the organic material in soils that are extremely necessary for the production, especially in those that are modified for beans. At San Joaquín community, Bolívar canton, Carchi province, this project was carried out with the objective of: evaluating the response of the agronomic behavior of two varieties of beans, the Cargabello Seleccionado and the Rojo del Valle (Phaseolus vulgaris L), being exposed at three doses of compost; 25 kilograms, 35 kilograms and 45 kilograms. The Complete Blocks Randomized Design was used (CBRD) in factorial arrangement (A x B) +2 with eight treatments and three repetitions, giving a total of 24 experimental units. The total area of the experiment was 495.04 m2. Germination percentage, plant height, stem diameter, days to flowering, number of pods per plant, number of grains per pod, and yield per net area of the experimental unit, were evaluated. The data were subjected to the analysis of variance while the comparison of the treatments was done with the Tukey test at 5%. According to the experimental work that was carried out in the land, the results of this project shown that the cultivation of Rojo del Valle, a variety of beans, with 35 kilograms of compost, has reached the highest of the economic yields.